PUNTOS DE VISTA EN LA NOVELA LUCIO O EL ASNO - Puche López, María del Carmen (Myrtia, 1987)
Regarding the choice of a certain point of view in a work, one can pose several questions: Is there a single perspective in the work? Is this perspective consistently maintained throughout the wole narration? Does the author reveal his own opinions? These aspects and others, such as the technique of anticipation, are those on which we have focussed our attention in this article about the Greek novel 'Lucius or the Ass'.